Minimally Access Surgery: Laparoscopy and Instrumentation in Veterinary Surgery - Tolga Tosun; Mustafa Kul; Fahrettin Alkan (European Journal of Multidisciplinary Health Sciences, 2026)
This review aims to comprehensively examine the basic equipment of veterinary laparoscopy and its use in the veterinary field. Laparoscopy is a minimally invasive surgical method that allows the visualization of the gastrointestinal and urogenital organs through small incisions made in the abdominal wall for both diagnostic and operative purposes. Technological advancements in imaging chain and surgical equipment have made laparoscopic applications more common and reliable. Important developments have been made in the historical process. In particular, the identification of pneumoperitoneum, the development of optical systems and the discovery of safe insufflation methods have taken laparoscopy beyond a diagnostic method and turned it into a surgical approach. Modern laparoscopic systems; Optical telescopes work with an integrated imaging chain consisting of high-intensity light sources, camera systems and monitors. In addition, various surgical equipment such as trocars, forceps, scissors, retractors and energy devices allow minimally invasive interventions to be performed effectively and safely. The main advantages of laparoscopy include smaller incisions, reduced postoperative pain, faster recovery process, and short hospitalization. These features make laparoscopy an important alternative for veterinary surgeons in both diagnostic and operative applications. In conclusion, laparoscopy is a safe and effective minimal access surgical method that is increasingly finding its place in veterinary surgery with technological advancements.